2017
DOI: 10.1111/jdv.14695
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tofacitinib for moderate‐to‐severe plaque psoriasis: a systematic review and meta‐analysis of randomized controlled trials

Abstract: The effects of tofacitinib in treating moderate-to-severe plaque psoriasis were unclear. We aimed to assess the effects of tofacitinib in treating moderate-to-severe plaque psoriasis. We searched PubMed, Cochrane Central Register of Controlled Trials and EMBASE for relevant randomized controlled trials (RCTs) and conducted a systematic review and meta-analysis. Four RCTs with 2724 participants were included. Compared to placebo, tofacitinib significantly improved psoriasis {≥75% reduction in the Psoriasis Area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…Both drugs have been approved for PsA since then . Tofacitinib is not included within the oral small molecules (OSM) category since its benefit/risk profile differs from that of the rest of the OSMs, especially with regard to risks , and consistent with its being considered separately in other treatment guidelines . Additionally, the panel addressed alternatives in patient subpopulations (e.g., patients with predominant enthesitis, axial disease, dactylitis, comorbidities), and greater versus lesser disease severity.…”
Section: Methodsmentioning
confidence: 99%
“…Both drugs have been approved for PsA since then . Tofacitinib is not included within the oral small molecules (OSM) category since its benefit/risk profile differs from that of the rest of the OSMs, especially with regard to risks , and consistent with its being considered separately in other treatment guidelines . Additionally, the panel addressed alternatives in patient subpopulations (e.g., patients with predominant enthesitis, axial disease, dactylitis, comorbidities), and greater versus lesser disease severity.…”
Section: Methodsmentioning
confidence: 99%
“…Tofacitinib 10 mg was found to be non-inferior to etanercept, but tofacitinib 5 mg was not shown to be non-inferior to etanercept. 32 Although study results demonstrated that both the 5 mg and 10 mg doses were effective in treating plaque psoriasis, [33][34][35] the 10 mg dose was proven to be more efficacious. 36 However, this higher dose is associated with increased safety concerns, leading the FDA to decline approval of tofacitinib for moderate-to-severe plaque psoriasis.…”
Section: Psoriasis Clinical Trialsmentioning
confidence: 99%
“…Treatment with IFN-α, an important cytokine in the pathogenesis of both vitiligo and psoriasis, for HCV and HBV infection can induce both psoriasis and vitiligo [ 129 , 130 , 131 ]. Moreover, narrow band ultraviolet B phototherapy and Janus kinase inhibitor can be used for treating both psoriasis and vitiligo [ 132 , 133 , 134 ].…”
Section: The Risk Of Autoimmune Diseases In Psoriasis and Psoriatimentioning
confidence: 99%